Cover Image, Volume 14, Issue 3. (10th June 2022) - Dong, Shuang‐lin; Dong, Yun‐wei; Cao, Ling; Verreth, Johan; Olsen, Yngvar; Liu, Wen‐jing; Fang, Qi‐zhi; Zhou, Yan‐gen; Li, Li; Li, Jing‐yu; Mu, Yong‐tong; Sorgeloos, Patrick
Abstract : The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 Abstract : The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648